A Flipped Classroom Curriculum for Milestones Preparation: Evidence to Support Active Learning. (October 2015) - Morgan, Helen; Chapman, Chris; Fitzgerald, Tom; Hammoud, Maya
Abstract : PURPOSE: Compare student satisfaction with the flipped classroom to traditional didactic sessions. BACKGROUND: Creating a flipped classroom curriculum for a 4-week residency preparation elective will allow examination of knowledge gains for content delivered by the flipped classroom curriculum compared with traditional lecture using the Association of Professors of Obstetrics and Gynecology (APGO) Preparation for Obstetrics and Gynecology Residency Knowledge Assessment. METHODS: A flipped classroom curriculum was created for the Advanced Clinical Skills in Obstetrics and Gynecology residency preparation elective for fourth-year medical students. These 14 sessions covered 75% of the Medical Knowledge content of the Accreditation Council for Graduate Medical Education (ACGME) level 1 milestones, with the remainder of the content taught using traditional lectures. The APGO Knowledge Assessment was administered on the first and last day of the course. The improvement in knowledge gains on content that was taught by the flipped classroom compared with traditional lecture sessions was determined by multivariate analysis. RESULTS: All 13 students enrolled in the course completed the pretests and posttests, and there was significant improvements in knowledge for content delivered by both flipped classroom and traditional lecture format. The score improvement for the flipped classroom content (pretest: 64%, posttest: 70%) was greater than for the lecture format (pretest 70%, posttest: 73%) ( P =.04). Student satisfaction was higher for the flipped classroom sessions than traditional didactics ( P <.05). DISCUSSION: The flipped classroom curricular model provided an excellent platform for preparing fourth-year medical students for ACGME Milestones level one knowledge competencies.